PERAN ORANG TUA SIGNIFIKAN TERHADAP KESIAPAN ANAK MENGHADAPI MASA PUBERTAS - Putri Utami, Desi; Mawarti, Retno; Susanti, Dwi (Universitas Jenderal Achmad Yani Yogyakarta, 2014)
Background: Puberty is a crucial time where a child has a rapid growth physically, psychologically and emotionally. The children who are ready to face the puberty will appear confident and comfort, on the other hand those who have difficulty to face the puberty will appear insecure and not confident. The parentsâ support hoped helped the children to be ready to face the puberty. Objectives: To determine the relation between parentsâ support and children readiness to face the puberty of the student in 5th year and 6th year of Elementary School 1 Reco, Kertek, Wonosobo. Methods: This research is descriptive analitic with cross sectional. The sample were taken by total sampling pairing, which took all the 68 students and their parents of 5th and 6th year of Elementary School 1 Reco, Kertek, Wonosobo. The used instrument is questionaire whose validity and realibility has already tested. The used data analizing is chi square, with significance Î±=0,05. Result: The support of the parents are in good range,the support of the family in facing physical change 57,4%, psychological 73,5% and sexually 41,2%. Most of the students of Elementary School 1 Reco, Kertek, Wonosobo about 67,6% are ready to face the puberty. Conclusion:A positive and significant relation are found bertween the support of the parents and the children readiness to face the puberty, it is based on significantcy p=0,000<0,05 with the strength of the relation is average (C=0,454) in phsical changes, significantcy p=0,003<0,05 with the strength of the relation is average (C=0,379) in psychosocial changes, and in sexual changes with the strength of the relation is average (C=0,553). Suggestion: The children considered ready to face the puberty because that is a normal phase and every person will face it in their childhood, also the parents must support of their children to face the puberty. Keywords: Role, parents and puberty